SUBSURFACE STRUCTURE IDENTIFICATION IN BATUI REGION USING SECOND HORIZONTAL DERIVATIVE ANALYSIS AND FORWARD MODELLING - Yondo (NIM 123 02 012) , Arif
Abstract : Batui region is an area which has a potential to become an oil field. This potential indicated by several oil and gas leaks in the surface. To prove this hypothesis, gravity survey have been carried out in the area to describe the condition of the subsurface structures. To obtain better description of subsurface structures, spectrum analysis has been done to obtain the depth of regional and residual anomaly source. Other than spectrum analysis, Second Horizontal Derivative analysis also has been done to obtain the information about the type of structure such as fault in the area. The results of the analysis combined with geology data give more accurate result. The Final result of this research is the prospect of the area to become oil field and the geology structures that have significance role in it.